Nomenclatural notes in Physostemon (Cleomaceae) - Roalson, Eric H.; Soares Neto, Raimundo Luciano (Phytotaxa, 2020)
Physostemon (Cleomaceae) includes 15 taxa in 10 species distributed from Mexico and the Caribbean south to Brazil and Paraguay. A full nomenclatural synonymy is presented including 7 lectotypes and 5 new combinations. Mitostylis species are moved to Physostemon based on morphological and molecular phylogenetic evidence. A table of characteristics for differentiating species is included.